The distributions and geochemical implications of methylated 2-methyl-2-(4, 8, 12-trimethyltridecyl)chromans in immature sediments. Issue 1 (January 2022) - Wang, Xin; Li, Meijun; Fang, Ronghui; Lai, Hongfei; Lu, Xiaolin; Liu, Xiaoqiang
Methylated 2-methyl-2-(4, 8, 12-trimethyltridecyl)chromans are salinity-sensitive biomarkers that have been detected in immature – early mature petroleum and sediments. In this study, the occurrence and distribution patterns of 2-methyl-2-(4, 8, 12-trimethyltridecyl)chromans were investigated in a set of lacustrine sediments from Nördlinger Ries of southern Germany and marine sediments from the South China Sea. Among all of the 2-methyl-2-(4, 8, 12-trimethyltridecyl)chroman isomers detected, 8-Me-2-methyl-2-(4, 8, 12-trimethyltridecyl)chroman presented with high abundance in sediments deposited in hypersaline environments, while absent in samples from normal marine environments. In contrast, 5, 7, 8-triMe-2-methyl-2-(4, 8, 12-trimethyltridecyl)chroman was more enriched in sediments from marine environments. This study also showed that the ratio of 5, 7, 8-triMe-/5, 8-diMe-2-methyl-2-(4, 8, 12-trimethyltridecyl)chroman can be applied as a potential salinity indicator on account of a positive correlation with other 2-methyl-2-(4, 8, 12-trimethyltridecyl)chroman salinity indicators. This ratio can be an alternative indicator of paleosalinity when 8-Me-2-methyl-2-(4, 8, 12-trimethyltridecyl)chroman is absent or present in quite low abundance. The content of 2-methyl-2-(4, 8, 12-trimethyltridecyl)chroman isomers may be affected by freshwater supply and lithology. Molecular simulations showed that 5, 8-diMe-2-methyl-2-(4, 8, 12-trimethyltridecyl)chroman has a higher thermal dynamic stability than 7, 8-diMe-2-methyl-2-(4, 8, 12-trimethyltridecyl)chroman. Thus, the ratio of 5, 8-diMe-2-methyl-2-(4, 8, 12-trimethyltridecyl)chroman/7, 8-diMe-2-methyl-2-(4, 8, 12-trimethyltridecyl)chroman may be a potential maturity parameter for sediments at a low thermal mature stage.